Design And Prototype Development Of A Low-Cost Face Touch Prevention Wearable For Covid19 - Nor Azlinah Md Lazam; Syaiful Anas Suhaimi; Noor Fadzillah Azman; Syahril Anuar Idris (Proceeding of International Conference on Science, Health, And Technology, 2022)
In preventing the spread of the Coronavirus, one of the protection measures for everyone is to avoid touching their eyes, nose and mouth, as advised by the World Health Organization (WHO) in their website. Viruses are easily picked up by our hands after touching many surfaces on daily basis. Once it is contaminated, our hands can transfer the virus to our eyes, nose or mouth where the virus can easily enter our body. The aim of this research is to develop a commercialized low-cost wearable called the Cov19-donttouch that alerts people from touching any parts of their face. The device is designed to mimic a choker or a brooch or a detachable device that will be placed near the neck area to sense the hand movement and will vibrate when a person is trying to touch their face. Cov19-donttouch uses low-cost motion detection sensor and vibrating motor as its main components. Through induction, the motion detection sensor detects human body movement (in this project: hand) and sends trigger to the buzzer that is connected to a sensor output pin. The sensor works well under one’s shirt or hijab for hand movement detection. The development of the device is achieved as Cov19-donttouch is a stand-alone wearable device where it does not need smart phones or smart watches to function. The device is equipped with battery as its power supply. All the components are encapsulated in a case produced using the 3D printer. Filament ABS is chosen for its durability and versatility as these are very important aspects since the device will be worn outside. ABS provides strength and higher temperature resistance. The Cov19-donttouch device will be placed on the neck to mimic a choker and it performs its intended function well.